PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN KUALITAS HUBUNGAN ATASAN - BAWAHAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR GURU DI JUBILEE SCHOOL - Rahim, Ramina (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
The purpose of this study is to analyze the effect of job satisfaction, organizational commitment, and leader member exchange on organizational citizenship behavior of teachers in Jubilee School. The population in this study were all teachers at Jubilee School in 2019. By using the census sample technique, the sample for this study were all teachers at Jubilee School in 2019, totaling 83 respondents. Methods of data collection using survey methods, with the research instrument is a questionnaire. The data analysis method uses the Structural Equation Model Partial Least Square (SEM PLS). This study proves that job satisfaction has a positive and significant effect on organizational citizenship behavior. Organizational commitment has a positive and significant effect on organizational citizenship behavior and leader member exchange has a positive and significant effect on organizational citizenship behavior